Practice, knowledge and perceptions of antenatal care services among pregnant women and nursing mothers in Southwest Nigeria (2013)
High maternal death in Nigeria is a concern to public health practitioners. Knowledge and perception of antenatal care (ANC) by pregnant women and nursing mothers are important in usage of ANC facilities. This study bridged existing gap in inadequate report of perception and knowledge about ANC services. We conducted cross-sectional study among 460 randomly selected pregnant women and nursing mothers in Okitipupa local government area and used questionnaire to collect data on antenatal issues. ANC Knowledge was measured using point scores. We analyzed the data using descriptive statistics and Chi-square test (α=5.0%). Almost two third of respondents (64.1%) had negative perception about ANC. ANC know ledge of about 15% was good, 61.1% moderate and 58(12.9%) was low. Age, husbands’ education level, place of ANC ser vice, sources of information about ANC were significantly associated to knowledge and perceptions of ANC. Knowledge and utilization of ANC were high, but perception was inadequate.